Small Run-of-River Dams Affect Taxonomic and Functional β-Diversity, Community Assembly Process of Benthic Diatoms - Wang, Yixia; Wu, Naicheng; Tang, Tao; Zhou, Shuchan; Cai, Qinghua (Frontiers in Ecology and Evolution, 2022)
Being increasingly constructed worldwide, dams are a main driver of flow regime change and biodiversity decline. Although small run-of-river dams have exceeded the number of large dams, their impacts on taxonomic and functional β-diversity as well as community assembly process of aquatic organisms have been largely neglected. 90 sites within 23 small run-of-river dams in the Xiangxi River were selected, and the hydrological and physicochemical variables for each site were measured. We analyzed the traits and β-diversity of benthic diatoms, and explored the key driving mechanism of benthic diatom community assembly. Our results indicated that the construction of small run-of-river dams could affect the β-diversity of benthic diatoms and the mechanism of community assembly. Specifically, we found that small run-of-river dams could change the relative contribution of nestedness components to the trait-based β-diversity of benthic diatoms, but generally the taxonomy-based β-diversity was relatively higher than the trait-based β-diversity. Furthermore, the community assembly process of benthic diatoms was also affected. In areas affected directly by small run-of-river dams, dispersal assembly was the key mechanism for community assembly. Compared to unregulated habitats, the dispersal assembly process between the impacted and the unregulated habitats has been enhanced. We advocate that this study can be expanded to other organisms (such as macroinvertebrates, phytoplankton, fish) in future to fully understand impacts of small run-of-river dams on biodiversity from a multi-trophic level aspect. Based on our results, we suggest that maintaining genetic and ecological connectivity based on an effective impact assessment in dry seasons is a potential solution to mitigate the impacts of such dams, as key to adaptive management and sustainability.